Perancangan Backend Sistem Pemilihan KRS (Mata Pelajaran Peminatan) Berbasis Website di SMAK Yos Sudarso Batam - Micheal Micheal; Fredian Simanjuntak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
This research aims to develop a web-based Study Plan Card (KRS) System for SMAK Yos Sudarso Batam. Currently, the KRS process still utilizes a digital questionnaire in the form of a Google Form, which is less efficient and accurate. Therefore, the author constructs a web-based system using PHP Laravel, employing the Web Development Life Cycle (WDLC) approach. This web-based KRS system enables students to perform the KRS process online, access class schedules, and view the availability and quotas of subjects. Teachers and school administrators can efficiently manage and monitor the KRS process. This development is expected to provide benefits such as time and resource efficiency, data accuracy, ease of access, and an enhanced user experience in arranging schedules and selecting subjects.